LapTrain: multi-modality training curriculum for laparoscopic cholecystectomy : results of a randomized controlled trial - Kowalewski, Karl-Friedrich; Proctor, Tanja; Preukschas, Anas; Friedrich, Matthias; Müller, Philip C.; Kenngott, Hannes Götz; Fischer, Lars; Müller, Beat P.; Nickel, Felix (Surgical endoscopy and other interventional techniques, 2018)
Multiple training modalities for laparoscopy have different advantages, but little research has been conducted on the benefit of a training program that includes multiple different training methods compared to one method only. This study aimed to evaluate benefits of a combined multi-modality training program for surgical residents.
Gesehen am 27.01.2020